2005
DOI: 10.1128/aem.71.1.423-427.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Direct Electric Current on the Cell Surface Properties of Phenol-Degrading Bacteria

Abstract: The change in cell surface properties in the presence of electric currents is of critical concern when the potential to manipulate bacterial movement with electric fields is evaluated. In this study, the effects of different direct electric currents on the cell surface properties involved in bacterial adhesion were investigated by using a mixed phenol-degrading bacterial culture in the exponential growth phase. The traits investigated were surface hydrophobicity (measured by adherence to n-octane), net surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 19 publications
6
45
1
4
Order By: Relevance
“…Similar results were previously reported [8] for phenol degrading bacteria in the presence of high electric current. A bioelectrokinetic test suggested that bacterial inactivation might occur by interaction with the surfaces of the electrodes, resulting in cell wall or membrane degradation through oxidation or reduction.…”
Section: Influence Of the Electric Potential On The Efficiency Of Thesupporting
confidence: 92%
See 1 more Smart Citation
“…Similar results were previously reported [8] for phenol degrading bacteria in the presence of high electric current. A bioelectrokinetic test suggested that bacterial inactivation might occur by interaction with the surfaces of the electrodes, resulting in cell wall or membrane degradation through oxidation or reduction.…”
Section: Influence Of the Electric Potential On The Efficiency Of Thesupporting
confidence: 92%
“…A bioelectrokinetic test suggested that bacterial inactivation might occur by interaction with the surfaces of the electrodes, resulting in cell wall or membrane degradation through oxidation or reduction. The cell viability may be also affected, at high applied potential or induced field, by irreversible permeabilization of the cell membrane which results in direct oxidation or reduction of the cellular constituents [8,9].…”
Section: Influence Of the Electric Potential On The Efficiency Of Thementioning
confidence: 99%
“…Similar observations have been reported [12,21,35]. Nevertheless, the pH across soil bed was generally maintained between 6.8 and 7.5 which were still favourable for the autochthonous microbial activity; this was possible due to regular reversal of current intensity [12,35].…”
Section: Change In Soil Phsupporting
confidence: 74%
“…Above the 3 days of remediation period, the pH started to increase gradually to 6.83, 7.0 and 7.25 near the anode section and began to decrease to 7.5, 7.6 and 7.7 near the cathode section while it increased to 7.21, 7.35 and 7.50 at 4 cm distance and 7.39, 7.45 and 7.56 at 7 cm distance, respectively, at the end of 15 days of remediation time. The variations in pH values (decrease and increase) observed around the anode section, 4 and 7 cm distances from anode and the cathode section may be due to the migration or movement of acidic and alkaline pH front from one electrode section to the other electrode section [21,35].…”
Section: Change In Soil Phmentioning
confidence: 99%
“…At the same time, the surface of the GAC was rich in microorganisms and the formation of this biological cathode greatly reduced mass transfer resistance, facilitating electron transfer from the solution to the electrode [25], so that electrons could move with high efficiency, and the removal efficiency increased. However, high current (more than 20 mA) may inactivate the microorganisms [26] and cause them to fall off [27]. In our experiment, the removal efficiency increased when the external voltage rose from 0.5 to 2 V; the current rose from 0.68 to 1.83 mA; and we did not find microbial inactivation or fall-off.…”
Section: X-3b Removal Efficiencies Under Different External Voltagescontrasting
confidence: 55%